Respuesta :
Answer:
m =-7
Step-by-step explanation:
1/9 (2m - 16 ) = 1/3 (2m + 4)
Multiply each side by 9 to get rid of the fractions
9*1/9 (2m - 16 ) =9* 1/3 (2m + 4)
2m-16 = 3(2m+4)
Distribute
2m-16 = 6m +12
Subtract 2m from each side
2m-16 -2m = 6m-2m +12
-16 = 4m +12
Subtract 12 from each side
-16-12 = 4m+12-12
-28 = 4m
Divide each side by 4
-28/4 = 4m/4
-7 =m
Answer:
m = -7
Step-by-step explanation:
1/9 (2m - 16 ) = 1/3 (2m + 4)
(2m - 16 ) = 9/3 (2m + 4)
2m - 16 = 3(2m + 4)
2m - 16 = 6m + 12
4m = -28
m = -7